Religião, música e humanização em Rubem Alves - Huff Júnior, Arnaldo Érico 20./21. Jh. (Numen, 2021)
This text deals with the place of music in Rubem Alves' thought and the humanizing potential of the aesthetic-musical experience. The key to dealing with this question is the idea of ​​beauty, developed by the author. Initially, we will deal with music as something that challenges and demands involvement and relationship. In this sense, there is a character of otherness and displacement in the musical experience. From this experience, finally, a pedagogical process of humanization unfolds. In religion and music, in the religious-musical experience, the humanizing force of beauty acts.